Dark-matter fermion from left-right symmetry - Ma, Ernest (2013)
In an unconventional realization of left-right symmetry, the particle corresponding to the left-handed neutrino νL [with SU(2)L interactions] in the right-handed sector, call it nR [with SU(2)R interactions], is not its Dirac mass partner, but a different particle which may be a dark-matter candidate. In parallel to leptogenesis in the SU(2)L sector, asymmetric production of nR may occur in the SU(2)R sector. This mechanism is especially suited for nR mass of order 1 to 10 keV, i.e. warm dark matter, which is a possible new paradigm for explaining the structure of the Universe at all scales.